Fracture toughness its role in engineering design - Hoeppner, David Dr; Marvin, Jeffrey; Thomson, Mary (Information Commons, University of Toronto, 1982)
Examines stress on materials and the role of design as it applies in mechanical, civil, and metallurgical/materials engineering